Exploring maritime Washington : a history and guide - Ebel, Erich R.; Fowler, Chuck (Charles Roy) (The History Press, 2023)
"Discover the popular destinations and hidden gems along Washington's coastline, from the Mukilteo Lighthouse to the Wedding Rocks petroglyphs and beyond. Learn about the seafaring Coast Salish people, who navigated the waters of the Pacific Northwest for thousands of years, and the early exploration and settlement by European-Americans in the late 18th century. Delve into the expansion and growth that led to the development of international ports and the modern maritime economy. View the enormous sternwheel snagboat, W.T. Preston--one of a trio that kept inland waterways navigable for nearly a century--and hundreds of other fascinating sites"--Cover.